Model Konteks Input Proses Produk dalam Evaluasi Pendidikan - Eko Budi Prasetyo (Fakultas Ilmu Pendidikan UNY, 2008)
Contexttual learning, and others represent the innovation idea which is looked into can fU(fill the requirement will the make-up of quality tnstruction: Various effort innovate the instruction more emphasizing in course ( linteraction activity. But, in the case of how teaming evaluation relevant not yet careful exhaustively. Model the evaluation / assessment by tes, especially objective tes which. during the time have so dominant in practice assessment result of learning presumably critical need and looked for alternative model the assessment result of learning oth.er. One of new evaluation model peeped out as the alternative model: Input Context Process the Product Keyword: model of the education evaluation